The effects of regional banks on economic resilience during the COVID-19 pandemic and the global financial crisis a cross-country comparison of the European countries - Franz Flögel; Tereza Hejnová (Institut Arbeit und Technik (IAT), 2021)
An economy's ability to resist adverse shocks, such as an economic recession or natural disaster, is associated with its financial system structure due to different countercyclical funding capabilities. This paper uses a novel database of bank headquarter locations in a cross-country comparison to investigate whether a decentralised geographical structure cushioned economic shocks during the COVID-19 pandemic and the global financial crisis (GFC). Findings suggest that the impacts of decentralisation differ between the two crises: while a greater spread of regional banks was associated with economic resilience during the GFC, countries with more centralised banking systems performed better in the first year of the pandemic. Future studies of pandemic recovery paths will show if regional banks have lost their ability for countercyclical funding, or if this non-financial crisis has rendered financial structure less important.
Keywords: G21; D82; O47; R58; H12; 330; COVID-19 pandemic; regional banks; soft information; economic resilience